Study of emotional intelligence using the Bar-on IQ inventory in students of the Faculty of Philosophy - Taramuel-Villacreces, James (2025)
Higher education faces challenges in the integral formation of students in an environment that demands emotional intelligence (EI) to manage complex situations. EI is essential for developing interpersonal skills, adaptability and stress management, which are fundamental for personal and professional success. Although research such as Thorndike's and Gardner's have explored social and emotional intelligence, they have not proposed specific methodologies to measure EI in the university context. This study adopts Bar-On's multifactorial model of EI, which combines emotional and social skills to cope with environmental pressures. Using a quantitative and descriptive approach, the Emotional Quotient Inventory (EQ-i)-S was used to assess five key dimensions of EI in 177 students in their last semesters at the Faculty of Philosophy of the Universidad Central del Ecuador, aged 17 to 65 years, of both genders. The Cronbach's alpha coefficient of 0.75 indicates acceptable reliability. The results showed variable levels of EI, with notable influence in the social, academic and professional spheres. It is recommended to create spaces for analysis between teachers and students to reflect on the results and work on problem areas. These initiatives should focus on developing emotional self-awareness, self-regulation and other interpersonal skills that strengthen the integral development of university students.